Ethical issues in the adoption and use of gamified library services: A narrative review and future research directions - Adeyemi, Ismail Olatunji (Business information review, 2025)
There has been a continuous increase and interest in the discussion regarding gamification in libraries and information centers. This necessitates the importance of discussing the ethical issues that concerns the adoption and use of gamified library services. This study adopts the narrative review approach to provide a discursive review of evidence of past literature, which were consulted both in libraries and the Internet. The study findings showed that ethical issues relating to the adoption of gamified library services include safety of data to be stored in the cloud, data integrity, prevention of manipulation and exploitation of librarians, avoidance of psychological discomfort, and so on. The study showed that ethical issues regarding the use of gamified library services include game overloading, cheating the game system, advantage for technology-savvy users, librarians’ autonomy and privacy, and so on. Future research directions in ethical issues in gamified library services were discussed.